2022
DOI: 10.1101/2022.03.22.485413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A CNN model for predicting binding affinity changes between SARS-CoV-2 spike RBD variants and ACE2 homologues

Abstract: The cellular entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) involves the association of its receptor binding domain (RBD) with human angiotensin converting enzyme 2 (hACE2) as the first crucial step. Efficient and reliable prediction of RBD-hACE2 binding affinity changes upon amino acid substitutions can be valuable for public health surveillance and monitoring potential spillover and adaptation into non-human species. Here, we introduce a convolutional neural network (CNN) model trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 125 publications
(177 reference statements)
0
4
0
Order By: Relevance
“… [60] SAS https://www.biosino.org/sas A platform which can predict the resistant effect of emerging variants and the dynamic coverage of SARS-CoV-2 antibodies among circulating strains. [61] STHAM https://github.com/uofu-ccts/prisms-comp-model-stham Spatio-temporal human activity model (STHAM), a kind of extended agent-based model which enables to simulate SARS-CoV-2 transmission dynamics. [67] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [60] SAS https://www.biosino.org/sas A platform which can predict the resistant effect of emerging variants and the dynamic coverage of SARS-CoV-2 antibodies among circulating strains. [61] STHAM https://github.com/uofu-ccts/prisms-comp-model-stham Spatio-temporal human activity model (STHAM), a kind of extended agent-based model which enables to simulate SARS-CoV-2 transmission dynamics. [67] …”
Section: Discussionmentioning
confidence: 99%
“…Spike protein Antigenicity for the SARS-CoV-2 (SAS) platform provided by Zhang et al [60] can predict the antigenicity of SARS-CoV-2 variants and help researchers better target immunobinding experiments to monitor the effectiveness of vaccine antibodies. Besides, Chen et al [61] predicted binding affinity of SARS-CoV-2 receptor binding domains or ACE2 with different amino acid substitutions by introducing a convolutional neural network (CNN) model for training on protein sequence and structural characteristics.…”
Section: Analysis Of the Mutation Antigen And Receptor Affinitymentioning
confidence: 99%
“…The interaction between ACE2 and RBD of Omicron BA.1, BA.2, and BA.3 was analyzed using docking and molecular dynamics (MD) simulations . Using an artificial intelligence model and docking simulation, it was shown that due to a higher binding ability to the host cell, Omicron is more contagious than the WT virus. , The artificial intelligence techniques were used to predict binding affinity changes between ACE2 and SARS-CoV-2 variants . The deep learning method was utilized to obtain the change in binding free energy caused by mutations in Omicron subvariants .…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 The artificial intelligence techniques were used to predict binding affinity changes between ACE2 and SARS-CoV-2 variants. 31 The deep learning method was utilized to obtain the change in binding free energy caused by mutations in Omicron subvariants. 32 Combination of MD simulation with the molecular mechanics Poisson–Boltzmann/generalized Born surface area (MM-PB/GBSA) methods can explain why Omicron BA.1 binds to ACE2 more strongly than the ancestral strain.…”
Section: Introductionmentioning
confidence: 99%